Label-free carbon quantum dots as photoluminescence probes for ultrasensitive detection of glucose1. Issue 84 (16th September 2015) - Qiao, Shi; Li, Haitao; Li, Hao; Liu, Juan; Kong, Weiqian; Hu, Qiaozhen; Huang, Hui; Liu, Yang; Kang, Zhenhui
<x xml:space="preserve">Abstract</x> Carbon quantum dots were demonstrated to be easy-to-use photoluminescence probes for the detection of glucose with fluorescence enhancement.